A comprehensive planning of private land transport for sustainable development and community welfare at Ayer Keroh, Melaka - Loo, Heoy Shin (2018)
One of the goals in Sustainable Development is to make cities and human settlements inclusive, safe, resilient and sustainable. In this study, the researcher focuses on the sustainable transport because the aim is to reduce the traffic congestion and reduce Green House Gases (GHG) emission from private transport in Ayer Keroh. Ayer Keroh is selected as the research location because it consists of residential, industrial, commercial, state government administrative centre and tourist spot which cause it to be crowded with vehicles such as private cars, motorcycle, lorry and busses. Thus, the high usage of private transportation leads to serious traffic congestion and high emission of GHG in Ayer Keroh. Although effort to promote green transportation to reduce usage of private transport and GHG emission, most of the public in Melaka still prefer the usage of private transportation due to several reasons. Hence, the problems of traffic congestion and emission of GHG could not be reduced significantly. Therefore, this study aims to examine the factors influence the public to use private land transport system, to investigate the strategies to change the public behaviour to reduce the usage of conventional private land transportation and propose a comprehensive private land transport planning for MPHTJ. Mixed Method research method is used in this research and the research design is exploratory, since the novelty of the research and MPHTJ does not implement any sustainable transport system at Ayer Keroh. Furthermore, the qualitative data collected from the interview sessions with the staffs in MPHTJ and local representatives able to provide insight of the possible factors, strategies and planning of sustainable private land transport system. The quantitative data is collected from the survey to triangulate with the data collected from the interview session. There were 22 respondents for the qualitative data collection and 700 respondents from the quantitative data collection. From the findings of this research, it shows that land use development pattern, demographics and vehicle ownerships are the critical factors to affect the usage of private transport. Therefore, the effective strategies to modify the behaviour of community to utilize the conventional private transport need to be identified in order to achieve the objectives of the research. Eventually, a comprehensive sustainable private transport system planning is constructed based on the findings. This research is important to promote Ayer Keroh to become a sustainable city in the future.